The marine diatom Thalassiosira rotula: chemical profile and antioxidant activity of hydroalcoholic extracts - Frleta Matas, Roberta; Popović, Marijana; Čagalj, Martina; Šimat, Vida (Frontiers in Marine Science, 2023)
The cosmopolitan centric diatom Thalassiosira rotula produces compounds in its natural habitat that can inhibit copepod reproduction. Moreover, it has been reported to possess compounds with therapeutic effects beneficial for health care. In this experiment, the extraction yield, total phenolic content (TPC), antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging ability, ferric reducing/antioxidant power (FRAP) and oxygen radical absorbance capacity (ORAC), and chemical profile by gas chromatography-mass spectrometry (GC-MS) analyses of T. rotula were investigated. Extractions were performed with 50% and 70% ethanol. A higher extraction yield [0.21 ± 0.01 g extract/g dry weight (DW) diatom] was observed for 70% ethanol. In addition, higher TPC (5.80 ± 0.32 mg gallic acid equivalents (GAE)/g DW diatom) and antioxidant activity [DPPH inhibition of 17.53% ± 0.56%, FRAP of 766.67 ± 34.69 µM Trolox equivalents (TE), and ORAC of 58.87 ± 2.03 µM TE] were observed for this extract. Myristic acid, palmitelaidic acid, palmitic acid, eicosapentaenoic acid, 24-methylenecholesterol, and docosapentaenoic acid were identified as dominant compounds in both extracts, while extraction in 70% ethanol yielded a higher content of fatty acids such as myristic acid, eicosapentaenoic acid, docosapentaenoic acid, and sterol 24-methylenecholesterol. Thus, it can be concluded that extraction of T. rotula with 70% ethanol improves antioxidant activity and provides a higher yield of compounds such as polyunsaturated fatty acids and sterols. Therefore, the species T. rotula could be considered a sustainable source of essential fatty acids and other bioactive compounds for further applications.